UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN MATHEMATICS LEARNING - Saadati, Farzaneh; Tarmizi, Rohani Ahmad; Ayub, Ahmad Fauzi Mohd (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2014)
Attention to integrate technology in teaching and learning has provided a major transformationÃ‚Â in the landscape of education. Therefore, many innovations in teaching and learning have beenÃ‚Â technology-driven. The study attempted to examine what is engineering studentsÃ¢â‚¬â„¢ perceptionÃ‚Â regarding the use of Information and Communication Technologies (ICT) in mathematicsÃ‚Â learning as well as investigate their opinion about how ICT can be integrated to improveÃ‚Â teaching and learning processes. The subjects were Iranian engineering students from twoÃ‚Â universities. The finding showed they are fully aware of importance of ICT in teaching andÃ‚Â learning mathematics. Whilst, they were feeling comfortable and confident with technology,Ã‚Â they do not have more experience of using technology in mathematics classes before. TheÃ‚Â findings supported the other studies, which indicated the potentials of ICT to facilitate studentsÃ¢â‚¬â„¢Ã‚Â learning, improve teaching, and enhance institutional administration as established in theÃ‚Â literature.Keywords: Technology, Mathematics Learning, Facebook, Attitude Toward ICTÃ‚Â DOI: http://dx.doi.org/10.22342/jme.5.2.1498.138-147